IMPLEMENTASI PENGELOLAAN RUANG TERBUKA HIJAU DI KOTA PEKANBARU DIKAITKAN DENGAN HAK ANAK - Iqbal, M. Satria Arde; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Green Open Space is a facility that must be a priority in the managementof an urban area. Based on Article 13 and 14 of Law Number 32 of 2004,management and control of the environment is the authority of the region, both inthe provinces and regencies or cities.Everyone has the right to a good and healthy environment because it ispart of human rights. Everyone has the right to get environmental education,access to information, access to participation, and access to justice in fulfillingthe right to a good and healthy environment. Just like children who also havehuman rights, the lack of play space makes children play more in the environmentthat cannot accommodate their needs. Article 4 number 2, 3 and number 6 of theMinister of Home Affairs Regulation Number 1 of 2007 concerning Urban GreenSpatial Arrangement, explained that green open spaces have benefits aseducational facilities, means of social interaction and facilities for socialactivities for children.Based on the problems raised, researchers use legal research methodsusing a sociological judicial approach, namely a research approach thatemphasizes the legal aspects (legislation) with regard to the subject matter to bediscussed, related to the reality in the field.The conclusion that can be obtained from the results of the study is thatthe maintenance and utilization of green open space cannot be said to be good,seen in terms of quality and quantity. There are several obstacles in themanagement of green open space in an effort to create quality green open spaces.There are also several efforts that will be made by the Pekanbaru Citygovernment in overcoming obstacles.key words: implementation, green open space, management, children's rights